A narratological experience using video on mobile devices - Gimenes, Roseli (International Journal of Humanities and Education Development (IJHED), 2020)
This work proposes to present technological hybridity in education in an experience developed with students of higher education in Languages using videos prepared through the Noizz application on mobile devices and presented at an event. This experience brought together teachers and students of the face-to-face and Distance Learning course, based on the studies of the Research Group Intercultural Encounters in Distance Learning - Life narratives from different Brazils.